Differential patterns of brain activation between hoarding disorder and obsessive-compulsive disorder during executive performance. Issue 4 (25th March 2020) - Suñol, Maria; Martínez-Zalacaín, Ignacio; Picó-Pérez, Maria; López-Solà, Clara; Real, Eva; Fullana, Miquel Àngel; Pujol, Jesús; Cardoner, Narcís; Menchón, José Manuel; Alonso, Pino; Soriano-Mas, Carles
Abstract: Background: Preliminary evidence suggests that hoarding disorder (HD) and obsessive-compulsive disorder (OCD) may show distinct patterns of brain activation during executive performance, although results have been inconclusive regarding the specific neural correlates of their differential executive dysfunction. In the current study, we aim to evaluate differences in brain activation between patients with HD, OCD and healthy controls (HCs) during response inhibition, response switching and error processing. Methods: We assessed 17 patients with HD, 18 patients with OCD and 19 HCs. Executive processing was assessed inside a magnetic resonance scanner by means of two variants of a cognitive control protocol (i.e. stop- and switch-signal tasks), which allowed for the assessment of the aforementioned executive domains. Results: OCD patients performed similar to the HCs, differing only in the number of successful go trials in the switch-signal task. However, they showed an anomalous hyperactivation of the right rostral anterior cingulate cortex during error processing in the switch-signal task. Conversely, HD patients performed worse than OCD and HC participants in both tasks, showing an impulsive-like pattern of response (i.e. shorter reaction time and more commission errors). They also exhibited hyperactivation of the right lateral orbitofrontal cortex during successful response switching and abnormal deactivation of frontal regions during error processing in both tasks. Conclusions: Our results support that patients with HD and OCD present dissimilar cognitive profiles, supported by distinct neural mechanisms. Specifically, while alterations in HD resemble an impulsive pattern of response, patients with OCD present increased error processing during response conflict protocols.